EFFECTS OF CURCUMIN AND NANOCURCUMIN ON CISPLATIN-INDUCED NEPHROTOXICITY IN RAT: COPPER TRANSPORTER 1 AND ORGANIC CATION TRANSPORTER 2 AS DRUG TRANSPORTERS - Rahmi, Deliana Nur Ihsani; Louisa, Melva; Soetikno, Vivian (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to investigate the efficacy of curcumin (CMN) and nanocurcumin (NC) at preventing cisplatin (CDPP)-induced nephrotoxicity. Methods: Two membrane transporters, copper transporter 1 (CTR1) and organic cation transporter 2 (OCT2), have been identified involved in active accumulation of CDPP into renal tubular cells. We analyzed OCT2 transcription levels in rat kidney tissue and determined whether renoprotective mechanism of CMN involves CTR1. Rats were randomly divided into five groups: (1) Control, (2) CDPP (7 mg/kg as single dose (i.p.), (3) CDPP+CMN (7 mg/kg CDPP as a single dose, i.p.+100 mg/kg/day of CMN), (4) CDPP+50 mg NC (7 mg/kg CDPP as single dose, i.p.+50 mg/kg/day NC), and (5) CDPP+100 mg NC (7 mg/kg CDPP as single dose, i.p.+100 mg/kg/day NC). Quantitative reverse transcription-polymerase chain reaction was performed to calculate relative expression of CTR1 and OCT2 genes in rat kidney. Results: Expression of CTR1 was unassociated with administration of CMN or NC, indicating CTR1 is uninvolved in renoprotective mechanism of CMN. The administration of 100 mg/kg/day NC increased expression of OCT2; this increase was higher compared with normal expression levels. This may be due to another regulatory mechanism from the CMN itself. Conclusion: NC has a better renoprotective effect compared with curcumin, suggested by the increased OCT2 expression on its administration in CDPP-treated rats.